Features of education and funding of German students in the context of the COVID-19 pandemic - Olha Nitenko (Університети і лідерство, 2020)
The article identifies the peculiarities of higher education in the Federal Republic of Germany during the crisis caused by the COVID-19 pandemic. First of all, it is the transition to distance learning and the loss of most students. The ways to overcome this crisis in the educational process are described: mass introduction of various video platforms for teaching, posting video lectures and electronic textbooks on university websites, creating groups of professors and higher education students in the WhatsApp messenger.